2009
DOI: 10.1093/annonc/mdn713
|View full text |Cite
|
Sign up to set email alerts
|

Management of hypertension in angiogenesis inhibitor-treated patients

Abstract: No clear recommendation for an antihypertensive agent can be made in this context because there is a lack of controlled studies addressing the subject. Blood pressure-lowering drugs should be individualized to the patient's clinical circumstances and angiogenic inhibitors should be withheld only from patients who experienced hypertensive crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
214
0
22

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(237 citation statements)
references
References 52 publications
1
214
0
22
Order By: Relevance
“…The mechanism(s) by which different chemotherapy agents induce hypertension is not fully understood. Potential mechanisms include vascular rarefaction (decrease in microvessel density), decreased sex hormones leading to impaired vasodilator and potentiated vasoconstrictor effects, and endothelial dysfunction causing an interference with nitric oxide (NO) signaling and thereby an increase in oxidative stress (Townsend et al, 2006;Jain et al, 2007;Izzedine et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism(s) by which different chemotherapy agents induce hypertension is not fully understood. Potential mechanisms include vascular rarefaction (decrease in microvessel density), decreased sex hormones leading to impaired vasodilator and potentiated vasoconstrictor effects, and endothelial dysfunction causing an interference with nitric oxide (NO) signaling and thereby an increase in oxidative stress (Townsend et al, 2006;Jain et al, 2007;Izzedine et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As hypertension is a risk factor for coronary heart disease, stroke, heart failure, and end-stage renal disease (Izzedine et al, 2009), an improved understanding of hypertension prior to starting chemotherapy, new-onset hypertension during and after chemotherapy, and factors influencing hypertension among cancer patients is paramount. Prior studies have focused on the prevalence of hypertension in cancer patients rather than incidence (Havlik et al, 1994;Satariano et al, 1994;Yancik et al, 2001;Ko et al, 2002;Piccirillo et al, 2004;Tammemagi et al, 2005;Smith et al, 2008), but the incidence of newonset hypertension is an important clinical outcome that requires investigation.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio retrospectivo de más de 25.000 pacientes con varios tipos de cáncer, que registraron una presión arterial (PA) normal al momento del diagnóstico (independientemente de sus anteceden-tes), casi un tercio desarrolló algún grado de HTA durante el tratamiento oncológico (32,16 casos por 100 personas/año) (7) . La mayoría desarrolló hipertensión moderada, pero 12,36 por 100 personas/año tuvieron cifras de PA sistólica entre 160 y 180 mmHg y 2,79 por 100 personas/año tuvieron cifras de PA sistólica mayores de 180.…”
Section: Convergencia Epidemiológicaunclassified
“…Además de la disminución del óxido nítri-co se han propuesto otros mecanismos como incremento de endotelina 1, rarefacción microvascular, activación del sistema renina angiotensina, estrés oxidativo, daño glomerular renal y aumento de la rigidez arterial de los grandes vasos. Es frecuente que, junto con la HTA, las drogas IA induzcan algún grado de proteinuria, aunque es raro que por sí solas afecten sostenidamente la función renal (16) .…”
Section: Inhibidores De Tirosina Quinasaunclassified
“…In individual phase III trials, incidences of grade 3/4 hypertension up to 17 % were reported with bevacizumab [7,11,17]. As early initiation of antihypertensive therapy may help to maintain treatment schedules [18,19] and reduce complications [20,21], identification of patients at high risk for bevacizumab-induced hypertension could be clinically valuable. Anti-angiogenic strategies are used increasingly for prolonged periods and/or in multiple treatment lines [4], and consequently the clinical importance of managing complications resulting from chronic blood pressure elevation might gain increased prominence.…”
Section: Introductionmentioning
confidence: 99%